Privatization and its aftermath: Are we facing a new displacement force? - Sharon Yavo-Ayalon (Journal of Urban Management, 2022)
The privatization of once publicly-funded affordable housing is the primary tool for preserving and maintaining affordable housing. This process, however, is quietly creating urban migration patterns that are altering the demographic profile of cities with cumulative change that we cannot fully estimate at this stage. There is growing need for a granular analysis at the parcel level to refocus the spotlight on this quiet displacement force. To start filling this lacuna, the article links privatization processes to gentrification and displacement. Through a case study of the privatization of Mitchell Lama buildings on Roosevelt Island, NYC, and the demographic changes it has engendered, this study points to a more significant trend of privatization of housing projects in American cities and worldwide. Its main argument is that, despite their quiet nature, which differs fundamentally from the Urban Renewal projects of the 1960s, the cumulative change they produce may be similar. On this basis, this study's main contribution is an in-depth, small-scale analysis aimed at deciphering the mechanisms, motivations, and decision-making processes of households experiencing ongoing privatization. Through a combination of ethnographic fieldwork, urban historical research, and statistical analysis, the study identifies three urban trends: 1. Privatization may lead to exclusionary displacement through increases in rent and cost of living; 2. Privatization may lead to social displacement pressures such as a sense of loss of place, loss of friends and community, and resentment among long-term residents; and 3. If the right policies are developed, privatization can present an opportunity for upward social mobility.
Keywords: 710; Affordable housing; Displacement; Gentrification; New York; Privatization